Non-communicable diseases impact low-income households in Malaysia. - Isamail, Norfatihah; Said, Rusmawati; Ismail, Normaz Wana; Haron, Sharifah Azizah (Penerbit Universiti Sains Malaysia, 2024)
Background: Non-communicable diseases (NCDs) have a vast and rising impact on households at all income levels across the globe, particularly with poorer people bearing the burden. Hence, this study examines NCDs’ effects on Malaysia’s B40 group (low-income earners). Methods: This study used the 2015 National Health and Morbidity Survey, a population-based cross-sectional survey with 18,616 respondents from B40 households in Malaysia. Logistic regression analysis is used to assess NCDs’ influence on poverty. Results: In 2015, more than 20% of the B40 households lived below the poverty level. In addition, the B40 households had a greater prevalence of NCDs, with almost half of them diagnosed with at least one NCD (47.32%); hypertension (9.90%), diabetes mellitus (17.12%) and hypercholesterolemia (22.89%). Households with a member having an NCD are more likely to experience poverty than those without NCDs. The results also suggested that B40 households with catastrophic payments were at a 25% threshold; the elderly, individuals without formal education and unpaid workers were more likely to experience poverty. Conclusion: The findings suggest that NCDs increase the likelihood of B40 households falling into poverty. These facts highlight the necessity of safeguarding B40 households from the financial burden of NCDs by creating more effective financial protection plans for Malaysia’s low-income earners.